2016
DOI: 10.1007/s00784-016-1725-3
|View full text |Cite
|
Sign up to set email alerts
|

The oral-systemic disease connection: a retrospective study

Abstract: The significance of the oral-systemic disease connection highlights the importance of preventing and treating oral disease which have profound medical implications on general health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…In the oral cavity, caries (World Health Organization [WHO] 2015) and periodontal diseases (World Dental Federation 2013) are examples of noncommunicable diseases (NCDs). A consistent relationship has shown between these oral diseases and other NCDs (Hujoel 2009; Joseph et al 2016; Kesim et al 2016). Obesity has been associated with caries (WHO 2015) and periodontal diseases (Keller et al 2015).…”
Section: Introductionsupporting
confidence: 70%
“…In the oral cavity, caries (World Health Organization [WHO] 2015) and periodontal diseases (World Dental Federation 2013) are examples of noncommunicable diseases (NCDs). A consistent relationship has shown between these oral diseases and other NCDs (Hujoel 2009; Joseph et al 2016; Kesim et al 2016). Obesity has been associated with caries (WHO 2015) and periodontal diseases (Keller et al 2015).…”
Section: Introductionsupporting
confidence: 70%
“…The relationship between oral and systemic diseases/conditions has been examined and is well documented; consequently, in recent years the relationship between physical frailty and oral hypofunction (deterioration of oral function) has also been examined, in various epidemiological studies. For example, it has been reported that sarcopenia, one of the core components of physical frailty, is associated with decline in occlusal force and mastication efficiency, with a significant odds ratio; there are also sex differences in the relationship .…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, these oral diseases cannot be used as a standard to measure oral health completely, because it ignores the multi-level characteristics of oral health and other impacts on quality of life [11]. For these reasons, that have prompted many researchers to examine the relationship between oral health and general health [12][13][14][15]. The correlation between oral health and general health has been proved by evidence, which is also mentioned in the World Health Organization report 2003 [10,16].…”
Section: Introductionmentioning
confidence: 99%